2023
DOI: 10.1038/s41419-023-05771-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement and targeted intervention of benzo(a)pyrene-regulated apoptosis related proteome modification and muti-drug resistance in hepatocellular carcinoma

Abstract: During the development of hepatocellular carcinoma (HCC), the mutual adaptation and interaction of HCC cells and the microenvironment play an important role. Benzo(a)pyrene (B[a]P) is a common environmental pollutant, which can induce the initiation of various malignant tumors, including HCC. However, the effects of B[a]P exposure on progression of HCC and the potential mechanisms remains largely uninvestigated. Here we found that, after the long-term exposure of HCC cells to low dose of B[a]P, it activated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…S2. These results are in correspondence to recent studies which have reported that CFA at concentrations of 20µM shows inhibitory effects on hepatocellular carcinoma [44].…”
Section: Resultssupporting
confidence: 92%
“…S2. These results are in correspondence to recent studies which have reported that CFA at concentrations of 20µM shows inhibitory effects on hepatocellular carcinoma [44].…”
Section: Resultssupporting
confidence: 92%
“…XIAP is an apoptotic protein that plays an important role in MDR by blocking the activation of the caspase cascade and promoting anti-apoptotic abilities [ 47 ]. Western blotting showed an obvious specific band in the Taxol® treated group, owing to chemotherapeutic stimulation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In ccRCC, abnormalities in mitophagy may be caused by various factors, including changes in the intracellular and extracellular environment, genetic mutations, and dysregulation of regulatory pathways ( 17 ). These abnormalities not only affect the survival and proliferation of tumor cells but may also impact tumor development, invasion, and drug resistance ( 18 ).…”
Section: Introductionmentioning
confidence: 99%